Chondritic ingredients: II. Reconstructing early solar system history via refractory lithophile trace elements in individual objects of the Leoville CV3 chondrite. (15th April 2018) - Patzer, Andrea; Hezel, Dominik C.; Bendel, Verena; Pack, Andreas
Abstract: We performed a LA‐ICP‐MS study of refractory lithophile trace elements in 32 individual objects selected from a single section of the reduced CV3 chondrite Leoville. Ingredients sampled include ferromagnesian type I and II chondrules, Al‐rich chondrules (ARCs), calcium‐aluminum‐rich inclusions (CAIs), a single amoeboid olivine aggregate (AOA), and matrix. The majority of rare earth element (REE) signatures identified are either of the category "group II" or they are relatively flat, i.e., more or less unfractionated. Data derived for bulk Leoville exhibit characteristics of the group II pattern. The bulk REE inventory is essentially governed by those of CAIs (group II), ARCs (flat or group II), type I chondrules (about 90% flat, 10% group II), and matrix (group II). Leoville matrix also shows a superimposed positive Eu anomaly. The excess in Eu is possibly due to terrestrial weathering. The group II pattern, however, testifies to volatility‐controlled fractional condensation from a residual gas of solar composition at still relatively high temperature. In principle, this signature (group II) is omnipresent in all types of constituents, suggesting that the original REE carrier of all components was CAI‐like dust. In addition, single‐element anomalies occasionally superimposing the group II signature reveal specific changes in redox conditions. We also determined the bulk chemical composition of all objects studied. For Mg/Si, Mg/Fe, and Al/Ca, Leoville's main ingredients—type I chondrules and matrix—display a complementary relationship. Both components probably formed successively in the same source region.